Reconciling rapid economic growth with environmental sustainability in Ireland - Clinch, J. Peter (Statistical and Social Inquiry Society of Ireland, 2001)
The extraordinarily rapid rate of growth of the Irish economy in the past decade has provided many benefits in terms of increased living standards and higher employment levels. However, economic growth has also resulted in increased pressures on the environment. This paper sets out to examine how the environment has fared over the period of unprecedented economic growth, and specifically, if the country?s environmental endowments have been improved or diminished by the substantial rise in income and wealth generated. Ireland's economic performance is summarised. Alternative definitions of environmental sustainability are examined briefly. The `weak sustainability? test is presented to assess how Ireland is faring from a macroeconomic perspective. The reliability of this test is assessed by looking, in a more detailed way, at individual indicators and their association with growth. The paper then turns to an assessment of environmental issues, including meeting: the Kyoto greenhouse assigned amounts; the acidification precursor amounts assigned via the Gothenburg Protocol; water quality objectives; waste emission reduction, recycling and re-use targets; accommodation needs. Individual attention is also given to the integration of environment and development in the following sectors: transport, energy, agriculture and forestry, tourism and industry. The paper outlines the salient features with regard to the environment of the existing policy mix. Finally, it examines what changes in environmental policy are likely to be desirable, with a particular emphasis on how market forces might better be mobilised to achieve environmental objectives.
Barrington Lecture 2000/2001
Read before the Society, 10 May 2001. '... delivered under the auspices of the Barrington Trust (founded by the bequest of John Barrington, Esq.) with the collaboration of the Journal of the Statistical and Social Inquiry Society of Ireland.' - p.1
Keywords: Economic growth and environmental policy; Sustainable development; 314.15